Methods of soccer teaching in sports training schools in Tunja, Boyacá (2017)
The present study issued from the academic activities carried out by the students of the degree program in Physical Education, Recreation and Sports of the University Foundation Juan de Castellanos in Tunja, Boyacá. The purpose of the study was to describe the methods of soccer education that are most used by coaches to instruct and train child athletes in the sports training schools in the city, during the training sessions held every week. The study involved twenty coaches who are members of sports clubs and sports training schools in soccer for child and youth categories. A methodology with a descriptive quantitative approach was implemented. The information was collected through a semi-structured survey, using a series of questions that were recorded in a file created for such purpose. The obtained data were processed with the Microsoft Excel 2016 program for its respective analysis. The results show that the coaches use and apply more, the method of mixed teaching, which is the combination of the analytical and global methods to impart the sports content of soccer.